Sentence Reduction For Justice Collaborators Based On Sema Number 04 Of 2011 In Corruption Crimes - Mauli Hutagalung, Jantarda; Widijowati, RR Dijan; Rayhan Amri, Athalariq (Greenation Research & Yayasan Global Resarch National, 2023)
Sentence reduction for Justice Collaborators in corruption cases is a reward or a gift for perpetrator who has collaborated with law enforcement officials in dismantling the case. When viewed in evidentiary theory, the reduction of punishment can be seen from the evidence of a Justice Collaborator in the trial. Based on the theory of justice, the granting of justice collaborator status is based on the judge's decision whereas the judge's decision is absolute in determining justice for what has been done by a justice collaborator, therefore the judge must see the efforts in the trial. This research was conducted with normative legal methods using legal literature materials consisting of theories, principles, legal principles, and laws and regulations related to and in accordance with this research. This research uses literature studies in the form of primary, secondary and tertiary legal sources. Results of this study: Justice Collaborators have an important role in uncovering corruption cases. For their role, justice collaborators are entitled to protection and a reduction in sentence period as stated in SEMA No. 04/2011. And two, the granting of justice collaborator status at trial is the absolute authority of the panel of judges. In this case, the panel of judges based on the facts at trial will consider whether the justice collaborator has a central role so that he can be declared the main perpetrator.